IgA-dominant postinfectious glomerulonephritis: a case report - Moreno-Alvarado, Rodolfo; Navarro-Blackaller, Guillermo; De Leon-Pérez, Werner; Armas-Eguizabal, David; Chávez-Iñiguez, Jonathan (Frontiers in Nephrology, 2023)
Introduction: Acute postinfectious glomerulonephritis (APIGN) is an immunological glomerular disease that is an important health issue in developing countries. The incidence remains high in developing countries with a male-to-female ratio of 2:1 and age predominantly above 50 years. In this case study, we present a patient with a history of Staphylococcus epidermidis infection, a past medical history of diabetes mellitus, and histopathological findings of APIGN with Immunoglobulin A (IgA) deposition. Methods: A 58-year-old male presented to the emergency room with a 6-day history of severe low back pain. Three days later, the patient developed fever, chills, abdominal pain in the upper quadrant and a subsequent lower limb cellulitis. Various immunological tests, imaging studies, and kidney biopsy were performed to arrive at a diagnosis. Results: Following the diagnosis and treatment of Cholangitis and Staphylococcus epidermidis, further investigation led to a diagnosis of IgA-dominant APIGN. IgA-dominant APIGN was treated with antibiotics, renin-angiotensin-aldosterone system inhibitors and steroids, and the patient was discharged from the hospital. Conclusion: In developing countries, APIGN is a relatively common presentation of kidney damage due to acute kidney injury and nephritic syndrome. IgA-dominant APIGN is a rare but increasingly recognized morphological variant in which IgA is the sole or dominant immunoglobulin. This unique presentation and multidisciplinary approach for diagnosing and treating IgA-dominant APIGN need to be considered and understood by healthcare professionals to better help these patients. Further investigation is needed to understand the best treatment of this IgA-dominant APIGN presentation and its prognosis.